Moral precaution in sources and derivatives - Mohamed Saleh Khalaf, Basim; Rahim Ali, Aqeel (Al-Adab Journal, 2020)
This paper deals with precautions in sources and derivatives, The sources came from: The source is from the abstract trio, the source is more than the trio, the meme source, the source of time and gender.I did not mention the name of the source, nor the industrial source, Because I did not stand on the precautions in them in the books of pure works until the eighth century AH, This is required by the research method.